Interactions “Candidatus Liberibacter solanacearum”—Bactericera cockerelli: Haplotype Effect on Vector Fitness and Gene Expression Analyses - Yao, Jianxiu; Saenkham, Panatda; Levy, Julien; Ibanez, Freddy; Noroy, Christophe; Mendoza, Azucena; Huot, Ordom; Meyer, Damien F.; Tamborindeguy, Cecilia (Frontiers in Cellular and Infection Microbiology, 2016)
“Candidatus Liberibacter solanacearum” (Lso) has emerged as a serious threat world-wide. Five Lso haplotypes have been identified so far. Haplotypes A and B are present in the Americas and/or New Zealand, where they are vectored to solanaceous plants by the potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Triozidae). The fastidious nature of these pathogens has hindered the study of the interactions with their eukaryotic hosts (vector and plant). To understand the strategies used by these pathogens to infect their vector, the effects of each Lso haplotype (A or B) on psyllid fitness was investigated, and genome-wide transcriptomic and RT-qPCR analyses were performed to evaluate Lso gene expression in association with its vector. Results showed that psyllids infected with haplotype B had significantly lower percentage of nymphal survival compared to psyllids infected with haplotype A. Although overall gene expression across Lso genome was similar between the two Lso haplotypes, differences in the expression of key candidate genes were found. Among the 16 putative type IV effector genes tested, four of them were differentially expressed between Lso haplotypes, while no differences in gene expression were measured by qPCR or transcriptomic analysis for the rest of the genes. This study provides new information regarding the pathogenesis of Lso haplotypes in their insect vector.